CompactDry "Nissui" ETC for Enumeration of Enterococci in a Variety of Foods: AOAC Performance Tested MethodSM 111902. (12th March 2020) - Mizuochi, Shingo
Abstract: Background: The CompactDry "Nissui" ETC is a ready-to-use dry media sheet using a chromogenic medium with selective agents for the detection and enumeration of Enterococcus spp. After a 20–24 h incubation at 37 ± 1°C, Enterococcus colonies appear blue. Objective: The performance of the CompactDry "Nissui" ETC was compared to that of the Nordic Committee on Food Analysis (NMKL) reference method 68, Enterococcus, Determination in Foods and Feeds, for 10 matrixes including cream, custard, lettuce, parsley, pasta salad, frozen ground beef patties, fresh cooked prawns, sandwiches, raw beef, and tuna pate. Methods: Performance indicators included repeatability, difference of means (DOM), robustness and inclusivity/exclusivity. Results: For all 30 materials (10 matrixes each inoculated at three levels), the relative standard deviation of repeatability (RSDr ) was <10% for both methods. Most materials yielded RSDr <5%, with five materials between 5 and 10% for the CompactDry "Nissui" ETC method and ten materials between 5 and 10% for the NMKL 68 method. The DOM ranged from –0.240 (95% CI–0.363, –0.118) to 0.228 (95% CI 0.041, 0.415) log10 CFU/g, well within the –0.5 to 0.5 log10 CFU/g range generally accepted as microbiologically insignificant. Both the reference method and this method have limitations of the species detected. Conclusions: The CompactDry "Nissui" ETC was validated for the enumeration of Enterococcus species in cream, custard, lettuce, parsley, pasta salad, frozen ground beef patties, fresh cooked prawns, sandwiches, raw beef, and tuna pate.